2017
DOI: 10.1590/1984-0462/;2018;36;1;00009
|View full text |Cite
|
Sign up to set email alerts
|

Rastreamento De Problemas De Saúde Mental Em Crianças Pré-Escolares No Contexto Da Atenção Básica À Saúde

Abstract: Objective: To study the applicability of the Strength and Difficulties Questionnaire (SDQ 2,4-p) as a screening tool for mental health problems in preschoolers, in the context of Primary Health Care; to evaluate the mental health problems of the sample, comparing data from SDQ (2,4-p) and from the Child Behavior Check List (CBCL 1½-5 years).Methods: Cross-sectional observational study with a convenience sample of 31-50-month-old children, whose caretakers provided informational reports. In the first stage, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
1
6
0
21
Order By: Relevance
“…Emotional symptoms, conduct problems, hyperactivity/inattention, peer-relationship problems and prosocial behaviors are assessed based on the 25 items answered in a Likert scale. Results found by Santos and Celeri 3 confirmed that the SDQ allows the identification of cases presenting problems within a “normal”, “borderline” or “abnormal” range in Brazil. In addition, they indicate significant and positive correlations between the scales of SDQ and preschool Child Behavior Checklist (CBCL/1.5-5), 6 which is another internationally known instrument for the assessment of small children’s behavioral problems.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Emotional symptoms, conduct problems, hyperactivity/inattention, peer-relationship problems and prosocial behaviors are assessed based on the 25 items answered in a Likert scale. Results found by Santos and Celeri 3 confirmed that the SDQ allows the identification of cases presenting problems within a “normal”, “borderline” or “abnormal” range in Brazil. In addition, they indicate significant and positive correlations between the scales of SDQ and preschool Child Behavior Checklist (CBCL/1.5-5), 6 which is another internationally known instrument for the assessment of small children’s behavioral problems.…”
supporting
confidence: 52%
“…The study of Santos and Celeri 3 about screening mental health problems in preschool children, which was published in the current edition of Revista Paulista de Pediatria , was developed with the aim of favoring an early assessment in the context of essential health care. The authors reinforce the importance of cultural adaptation of instruments that have been developed in other countries to facilitate the early identification of problems, 4 which results in better prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As quatro primeiras escalas formam o "total de problemas internalizantes" e as duas últimas formam o "total de problemas externalizantes". As sete escalas somadas formam o "total de problemas emocionais e comportamentais" (Santos & Celeri, 2018).…”
Section: Inventário De Problemas De Comportamento -Child Behavior Cheunclassified
“…Na infância e adolescência é o momento em que os circuitos neuronais dos jovens estão sofrendo constantes influências das experiências que a criança vivencia, gerando assim impactos no seu comportamento (Santos & Celeri, 2018). Nessa perspectiva, o confinamento interfere nas potencialidades das crianças, provocando dificuldades para a aquisição de novas habilidades e capacidades, além de prejudicar as interações e relações interpessoais dos jovens que são importantes na fase da infância e adolescência (Aydogdu, 2020).…”
Section: Introductionunclassified